Evaluation of tensile strength and surface topography of orthodontic wires after infection control procedures: An in vitro study - M Brindha; N Kurunji Kumaran; K Rajasigamani (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of this study is to evaluate, the influence of four types of sterilization/disinfection procedures (autoclave, hot air oven, glutaraldehyde, and ultraviolet [UV] light) on the tensile strength and surface topography of three orthodontic wires (stainless steel (SS), titanium - molybdenum alloy [TMA], and cobalt chromium (CoCr)). Materials and Methods: Sample comprised of three types of 8 inches straight length segments of orthodontic wires. They were divided into three groups according to wire composition comprising of 50 samples each. Totally 50 samples of each group were then equally divided into five subgroups according to sterilization method. After sterilization and disinfection of the experimental group, surface topography was examined with scanning electron microscope (SEM) and tensile strength was tested using universal testing machine. Result: The results of this study show that the mean ultimate tensile strength (UTS) of SS wire after four sterilization procedures were similar to the control group (1845.815 ± 142.29 MPa).The mean UTS of TMA wire increases after four sterilization procedures when compared with the control group (874.107 ± 275.939 MPa). The mean UTS of CoCr wire remains same after UV light disinfection, but increases after other three sterilization procedures when compared with the control group (1449.759 ± 156.586 MPa). SEM photographs of the present study shows gross increase in pitting roughness of the surface topography of all the three types of wires after four types of sterilization. Conclusion: Orthodontists who want to offer maximum safety for their patients can sterilize orthodontic wires before placement, as it does not deteriorate the tensile strength and surface roughness of the alloys.